Redevelopment of Kampung Hindu in Kesawan Area, Medan with the Behavioral Architecture Approach - Pane, Putri Sahara; Aulia, Dwira Nirfalini (Jurnal Koridor, 2020)
Based on Medan City Government 2012, slum areas in Medan City are currently estimated to reach 22.5% of the total area of ​​Medan City, which consists of 88,166 housing units or 13.62% of the total houses in Medan City. Moreover, this has an impact on public health. Responding to this problem, the need to design a residence by rebuilding a residential area would be better by not abandoning the customs and culture of the people in the area. The project location is in Medan, Kampung Kelurahan Kesawan. The design method that is carried out is the choice of design location and approach to problem-solving design or design stages. It expects that the results of the design can provide suitable space and occupancy for the community, such as the construction of high-rise villages and community areas.